2007
DOI: 10.1002/dneu.20361
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent formation and functions of chondroitin sulfate‐rich extracellular matrix of perineuronal nets

Abstract: Extracellular matrix molecules--including chondroitin sulfate proteoglycans, hyaluronan, and tenascin-R--are enriched in perineuronal nets (PNs) associated with subsets of neurons in the brain and spinal cord. In the present study, we show that similar cell type-dependent extracellular matrix aggregates are formed in dissociated cell cultures prepared from early postnatal mouse hippocampus. Starting from the 5th day in culture, accumulations of lattice-like extracellular structures labeled with Wisteria florib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
312
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(338 citation statements)
references
References 57 publications
20
312
5
1
Order By: Relevance
“…Finally, in the present study, the specificity of WFA lectin histochemistry for CSPGs is demonstrated by control experiments with chondroitinase ABC, an enzyme that degrades chondroitin sulfate glycosaminoglycan chains and is routinely used to investigate the effects of elimination of CSPGs (e.g. Crespo, et al, 2007, Dityatev, et al, 2007, Hamai, et al, 1997, Pizzorusso, et al, 2002, Sugahara, et al, 1994. In our chondroitinase ABC-treated tissue, we could detect no intracellularly-labeled glia, and only rare, faintly labeled perineuronal nets.…”
supporting
confidence: 58%
“…Finally, in the present study, the specificity of WFA lectin histochemistry for CSPGs is demonstrated by control experiments with chondroitinase ABC, an enzyme that degrades chondroitin sulfate glycosaminoglycan chains and is routinely used to investigate the effects of elimination of CSPGs (e.g. Crespo, et al, 2007, Dityatev, et al, 2007, Hamai, et al, 1997, Pizzorusso, et al, 2002, Sugahara, et al, 1994. In our chondroitinase ABC-treated tissue, we could detect no intracellularly-labeled glia, and only rare, faintly labeled perineuronal nets.…”
supporting
confidence: 58%
“…In line with our finding is the well-established observation that PNNs predominantly enwrap PV neurons in the cortex and hippocampus (Bruckner et al, 1996;Van den Oever et al, 2010), suggesting a shared molecular process that regulates condensation of structural ECM proteins at PV neurons in the cortex. Changes in PNNs have been shown to affect the firing properties of PV cells, thereby influencing GABAergic control over pyramidal cell activity (Dityatev et al, 2007). Indeed, in the mPFC, degradation of PNNs results in reduced inhibitory input onto pyramidal cells and this impairs acquisition of cocaine CPP memory (Slaker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar and DRG neurons were prepared from 5-to 7-d-old wild-type, TAG-1-, Contactin-, or Caspr-deficient mice as described previously (Chen et al, 1999;Kleene et al, 2001). Hippocampal neurons were prepared from 1-to 2-d-old wild-type mice (Dityatev et al, 2007) and neurons from spinal cord were prepared from 14-d-old wild-type embryos (Simova et al, 2006). Cortical neurons were prepared from 17-d-old wild-type embryos.…”
Section: Methodsmentioning
confidence: 99%